Te-seeded growth of few-quintuple layer Bi2Te3 nanoplates - Gao, Xuan P. A. (2015)
We report on a Te-seeded epitaxial growth of ultrathin Bi2Te3 nanoplates (down to three quintuple layers) with large planar sizes (up to tens of micrometers) through vapor transport. Optical contrast has been systematically investigated for the as-grown Bi2Te3 nanoplates on the SiO2/Si substrates, experimentally and computationally. The high and distinct optical contrast provides a fast and convenient method for the thickness determination of few-quintuple layer (QL) Bi2Te3 nanoplates. By aberration corrected scanning transmission electron microscopy, a hexagonal crystalline structure has been identified for the Te seeds, which form naturally during the growth process and initiate an epitaxial growth of the rhombohedral-structured Bi2Te3 nanoplates. The epitaxial relationship between Te and Bi2Te3 is identified to be perfect along both in-plane and out-of-plane directions of the layered nanoplate. Similar growth mechanism might be expected for other bismuth chalcogenide layered materials.